HPRT高活性Urat1-Uoxダブルノックアウトマウスの確立とキサンチン酸化還元酵素阻害剤の効果 - 内田, 俊也; 細谷, 拓司; 柴田, 茂; 富岡, 直子; 細山田, 真 (日本薬理学会年会要旨集, 2020)
It is known that there are species differences in the purine metabolic system between humans and rodents (e.g. urate oxidase (Uox), and hypoxanthine phosphoribosyltransferase (HPRT), etc.). URAT1 (SLC22A12) is renal urate (UA) reabsorption transporter and the target for UA-lowering therapies. In humans, URAT1 deficiency has a significant UA-lowering effect (ULE), but not in Urat1-knokout (KO) mice. The aim of this study is the establishment and urate kinetic profiling of high HPRT activity Urat1-Uox double knockout (DKO) mice and the investigation of the effect of xanthine oxidoreductase inhibitor (XOI), topiroxostat in this model mice. Topiroxostat 1 mg/kg (Top) was administered to DKO mice for 7 days by feeding diet. Oxypurines (UA, hypoxanthine and xanthine) and creatinine in plasma and urine were measured by HPLC. DKO mice showed a significant decrease in plasma UA levels, increased fractional excretion of UA (FEUA), and enhanced Top-induced ULEs, compared with Uox-KO only. Thus, high HPRT activity seems to be important for producing ULE by URAT1 inhibition. The combination therapy of URAT1 inhibition and XOI showed an effective ULEs, suggesting that it is useful for the treatment of hyperuricemia.